2017
DOI: 10.3390/su9101762
|View full text |Cite
|
Sign up to set email alerts
|

Risk Measurement and Risk Modelling Using Applications of Vine Copulas

Abstract: This paper features an application of Regular Vine copulas which are a novel and recently developed statistical and mathematical tool which can be applied in the assessment of composite financial risk. Copula-based dependence modelling is a popular tool in financial applications, but is usually applied to pairs of securities. By contrast, Vine copulas provide greater flexibility and permit the modelling of complex dependency patterns using the rich variety of bivariate copulas which may be arranged and analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Fischer et al [27] compared this approach with other methods and found that the vine copula method performed better in high-dimensional cases. Other studies [32][33][34] pointed out the same conclusion.…”
Section: Vine Copula Construction a K-dimensional Copulasupporting
confidence: 62%
“…Fischer et al [27] compared this approach with other methods and found that the vine copula method performed better in high-dimensional cases. Other studies [32][33][34] pointed out the same conclusion.…”
Section: Vine Copula Construction a K-dimensional Copulasupporting
confidence: 62%
“…See, e.g., Dißmann et al (2013) and references therein, Min and Czado (2014), Beare and Seo (2015), Brechmann and Joe (2015), Schepsmeier (2015), Weiß and Scheffer (2015), etc. Vine copula has been widely applied in finance, see, e.g., Low et al (2013), Weiß and Supper (2013), Abbara (2014), Arreola Hernandez (2014), Brechmann et al (2014), Markwat (2014), Allen et al (2014), Zhang (2014), Siburg et al (2015), etc. For example, it can be applied in portfolio optimization in mainly two directions.…”
Section: Introductionmentioning
confidence: 99%
“…Likert scales are known as a tool for the measurement and assessment of attitudes. The reason for this is that the Likert scale is a straightforward tool to use and can be analysed effectively as interval or fuzzy scales (Allen et al, 2017). Eckenrode (1965) presented seminal work on criteria weights elicitation.…”
Section: Brief Review Of Methodology Of An Integrated Delphic-eckenromentioning
confidence: 99%